1989
DOI: 10.1007/bf01399029
|View full text |Cite
|
Sign up to set email alerts
|

Parametric analysis of the isotope shift and hyperfinestructure in the Eu I configuration 4f 7 5d 6s

Abstract: With doppler-reduced /nter_modulated opto_galvanic _saturation laserspectroscopy (IMOGS) in Eu I the isotope shift (IS) and hyperfine structure (hfs) of the remaining baD term of the configuration 4 f v 5d6s was investigated. With the help of former measurements in our group (a6'l°D) and by other authors (aS'l°D) the IS of the now complete configuration (20 levels) was analysed with wavefunctions by J.-F. Wyart. From the parametric description of the IS resulted the necessity also to include the often neglecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…In the works encountered in the literature, devoted to the isotope shift for a europium atom, CSO parameters for the following configurations were determined: 4f 7 5d6s [13,15,17], 4f 7 6s7s [11], 4f 7 6s8s [14], 4f 7 6s6d and 4f 7 6s6p [16]. On the basis of the results obtained, it was also shown that the ratio between the obtained values of isotope shift parameters and the respective fine structure radial integrals is similar for all configurations.…”
Section: Isotope Shiftmentioning
confidence: 94%
See 2 more Smart Citations
“…In the works encountered in the literature, devoted to the isotope shift for a europium atom, CSO parameters for the following configurations were determined: 4f 7 5d6s [13,15,17], 4f 7 6s7s [11], 4f 7 6s8s [14], 4f 7 6s6d and 4f 7 6s6p [16]. On the basis of the results obtained, it was also shown that the ratio between the obtained values of isotope shift parameters and the respective fine structure radial integrals is similar for all configurations.…”
Section: Isotope Shiftmentioning
confidence: 94%
“…It is common in the case of a europium atom to relate the isotope shifts of the levels to the ground level 4f 7 6s 2 a 8 S 7/2 . Since in the case of the lines investigated, the lower levels were the levels belonging to the configuration 4f 7 5d6s, for which IS values with respect to the ground level are known from the literature, the isotope shifts of the upper levels were determined via addition of the measured shifts (upon subtraction of NMS) to the shifts of the lower levels (based on the data from [17]). The values obtained in this way are presented in column 12 of table 2.…”
Section: Calculation Of the Isotope Shifts Of The Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme of the experimental set-up for saturation absorption spectroscopy (SAS) in a hollow cathode change in the absorption of the "probe" beam is detected by a lock-in technique. The arrangement concerning the laser system is basically the same as described in [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…Until now the hyperfine structure (hfs) and the isotope shift (IS) of the levels belonging to configurations: 4 f 7 6s 6p [1][2][3], 4 / 7 5d 6p [-4, 5], 4 / 7 5d 6s [6][7][8][9][10], 4f76d6s [I1], 4f76s7s [12] and 4f76sSs [1][2][3][4][5][6][7][8][9][10][11][12][13] have been investigated with high accuracy by laser-spectroscopic methods in both stable europium isotopes 15~Eu and 153Eu" The hfs of the ground level 4 f 7 6s 2 SS7/z has been very accurately measured by atomic-beam-methods [-14, 15]. Recently Childs [16] using atomic-beam laser-rf double-resonance technique obtained also very precise values for the hfs splitting in ten 4f75d6s I°Dj and SDj levels of the ~ 51,153Eu I.…”
Section: Introductionmentioning
confidence: 99%